Complementarities and costly investment in a one-sector growth model - Thompson, Maria João Ribeiro (2007)
The presence of complementarities generally makes a growth model nonlinear, hence delivering multiple equilibria. Introducing internal investment costs in the R&Dbased growth literature, we develop a growth model which combines the assumptions of complementarities between capital goods in the production function and of internal costly investment in capital. We find that with such combination of complementarities and costly investment, the growth model delivers a single equilibrium.